A retrospective audit of nursing-related morbidity recorded in a state hospital in KwaZulu-Natal - Spumelelo P Nyide; Petra Brysiewicz; John Bruce; Damian L Clarke (AOSIS, 2019)
Background: Health care professionals are expected to deliver safe and effective health services; however there is increased realisation that adverse events in the health system are a major cause of preventable morbidity and mortality. Objectives: To conduct a retrospective audit of nursing-related morbidities in a state hospital in KwaZulu-Natal, South Africa. Method: A retrospective audit of nursing-related morbidities documented by the surgical service was carried out using the Hybrid Electronic Medical Registry data for a period of 3 years - 01 November 2013 to 31 October 2016. Results: There were a total of 12 444 admissions to surgical service during the study period, with 461 nursing-related morbidities reported. There was an increase in the number of documented nursing-related morbidities noted during November 2015 to October 2016, with 79% of all reported nursing-related morbidities documented during this period. A total of 54% of nursing-related morbidities were associated with males (n = 248) and 46% (n = 213) with females. The most commonly documented nursing-related morbidity was drugs/medication (n = 167, 36%) with the second most common being adjunct management (n = 130, 28%). Conclusion: The study has identified the most commonly documented nursing-related morbidities in the surgical service of a state hospital. The findings of the study could provide direction for further research and educational initiatives.